Polycation-Based Gene Therapy: Current Knowledge and New Perspectives - J. Tiera, Marcio; Shi, Qin; M. Winnik, Francoise; C. Fernandes, Julio (Current Gene Therapy, 2011)
At present, gene transfection insufficient efficiency is a major drawback of non-viral gene therapy. The 2 main types of delivery systems deployed in gene therapy are based on viral or non-viral gene carriers. Several non-viral modalities can transfer foreign genetic material into the human body. To do so, polycation-based gene delivery methods must achieve sufficient efficiency in the transportation of therapeutic genes across various extracellular and intracellular barriers. These barriers include interactions with blood components, vascular endothelial cells and uptake by the reticuloendothelial system. Furthermore, the degradation of therapeutic DNA by serum nucleases is a potential obstacle for functional delivery to target cells. Cationic polymers constitute one of the most promising approaches to the use of viral vectors for gene therapy. A better understanding of the mechanisms by which DNA can escape from endosomes and traffic to enter the nucleus has triggered new strategies of synthesis and has revitalized research into new polycation-based systems. The objective of this review is to address the state of the art in gene therapy with synthetic and natural polycations and the latest advances to improve gene transfer efficiency in cells
Keywords: reticuloendothelial system